Mechanical Properties of Bioactive Glass-Cordierite Composite - Ahmad Fakhruddin Mohd Mokhtar Kamil; Hamisah Ismail; Mohamad Hasmaliza (Archives of Metallurgy and Materials, 2023)
Bioactive glass (BG) can be utilized as a replacement and regeneration material for orthopaedic and orthodontic. However, a load-bearing structure requires good mechanical properties to withstand high stress, in addition to good bioactivity properties. In this research, BG and cordierite (BG-cord) composite was fabricated to improve BG’s mechanical properties. The mechanical strength of the BG-cord was investigated. Both BG and cordierite were synthesized separately using the glass melting method. The synthesized BG and cordierite powders were used to fabricate BG-cord using a composition variation from 10 to 50 wt.%. The composite with 30 wt.% cordierite demonstrated the highest diametral tensile strength (DTS), 14.01 MPa.